The Effect of Green Tea Extract Supplementation on PlasmaMalondialdehyde (MDA) in Human with Sub-Maximal PhysicalActivity, Double-Blind and Placebo-Controlled Trials - Arsana, Putu Moda; Sasiarini, Laksmi; Nugraha, Bayu Eka (UI Scholars Hub, 2019)
Introduction. Green Tea extract has been proven in vitro to have the ability as an antioxidant. Submaximal physical activity causes an increase in free radicals. The increase of MDA can detect the increase of free radicals. This study aimed to determine the effects of green tea extract supplementation against free radicals in submaximal physical activity by measuring plasma MDA. Methods. This double-blind controlled trial study was performed in 20 students of faculty of sports science with submaximal physical activity in the form of 1,500 meters running in 12 minutes using a treadmill. Subjects were divided into two groups: green tea extract group (250 mg) and the control group (placebo). Supplement/placebo was given as one caps a day for fourteen days before submaximal physical activity. The plasma MDA was taken before, 2 hours after, and 48 hours after the submaximal physical activity. Analysis of the results used ANOVA and post hoc Tukey. The study has been assessed by 24 | Jurnal Penyakit Dalam Indonesia | Vol. 6, No. 1 | Maret 2019 Putu Moda Arsana, Laksmi Sasiarini, Bayu Eka Nugraha Medical Research Ethical Committee at Medical Faculty of Universitas Brawijaya. Results. In the control group, the mean value of plasma MDA levels in basal conditions, 2 hours and 48 hours after submaximal physical activity were 52.43 nmol/ml (standard deviation [SD] 12.52 nmol/ml), 55.57 nmol/ml (SD 13.84 nmol/ml), and 63.86 nmol/ml (SD 12.17 nmol/ml), respectively. However, this result was not statistically significant (p = 0.158). In the treatment group, the mean value of plasma MDA level at 48 hours after submaximal physical activity was significantly decreased compared to basal condition with mean value in basal and 48 hours after submaximal physical activity were 36.14 nmol/ ml (SD 5.88 nmol/ml) and 19.86 nmol/ml (SD 8.92 nmol/ml), respectively (p <0.001). Further analysis showed a significant difference in plasma MDA levels between the two groups at basal, 2 hours, and 48 hours after submaximal physical activity (p values were 0.012; <0.001, and <0.001 respectively). Conclusion. Green tea extract can decrease the plasma level of MDA at basal, 2 hours, and 48 hours after submaximal physical activity.